1987
DOI: 10.1111/j.1479-828x.1987.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult Fetomaternal Haemorrhage As a Cause of Fetal Mortality and Morbidity

Abstract: Spontaneous fetomaternal haemorrhage is an important, but usually overlooked, cause of perinatal mortality and morbidity. Although fetomaternal bleeding in the third trimester of pregnancy is common it is normally less than 0.1 ml. A fetal macrotransfusion (greater than 5 ml) is uncommon, but is important because it is insidious, unexpected and usually occurs in completely normal pregnancies. This paper analyses the perinatal mortality and morbidity associated with occult fetomaternal haemorrhage at the Royal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The minimal amount of fetal blood transfused to the mother leading to a poor outcome is unknown [15] . A review of fetal death after FMH found a wide interval between 23 and 51% of the fetal blood volume [19] . The neurological prognosis after massive FMH was not evaluated and the consequence of the ane- mia on the fetal brain are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal amount of fetal blood transfused to the mother leading to a poor outcome is unknown [15] . A review of fetal death after FMH found a wide interval between 23 and 51% of the fetal blood volume [19] . The neurological prognosis after massive FMH was not evaluated and the consequence of the ane- mia on the fetal brain are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Most are diagnosed retrospectively after an infant is stillborn, experiences unexplained fetal distress or is born with symptoms consistent with a hemorrhage. 34 Prenatally, the mother may present with a history of decreased or absent fetal movement. 13 A 1997 study found in 27% of cases, decreased or absent fetal movement was the presenting symptom of a fetal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of pregnancies in which fetomaternal transfusion causes fetal death is about 0.04% (Laube & Schauberger 1982). The presenting symptom is often a decrease in fetal movements (Fliegner et al 1987). Avoidance of intrauterine death in a viable, nonmalformed fetus is clearly a vital part of antenatal care.…”
Section: Discussionmentioning
confidence: 99%